Develop a negativeand positive customer experience model in online retailing by study the differences between customer experience models in successful and failure situations - Al-Mashhadani, Adam Smayan Fayyadh (International Journal of Psychosocial Rehabilitation, 2020)
the study objectives are Develop a negative and positive customer experience model in online retailing by study the differences between customer experience models in successful and failure situations. The findings also show the importance of Internet instability, as it has a negative impact and contributes to adverse consumer expectations and responses, should be taken into consideration by corporations.